Nerve injury associated with high-intensity focused ultrasound: A case report - Angkana Sathaworawong (2019)
© 2017 Wiley Periodicals, Inc. Skin laxity is a common cosmetic concern in middle-aged women. High-intensity focused ultrasound (HIFU) is one of noninvasive modalities that provides safe and effective improvement in skin laxity and tightening with minimal adverse effects. Concerning an extensive use of HIFU for facial rejuvenation, dermatologists should be aware of potential adverse effects of HIFU treatment. We herein present a case of 33-year-old Thai female with facial nerve injury after HIFU treatment for skin laxity.